2020
DOI: 10.3329/ajmbr.v6i3.49788
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on fishersˊ livelihood in Kishoregonj haor region, Bangladesh

Abstract: Kishoreganjhaor region is highly sensitive to the climatic events such as flash flood, soil erosion, heavy rainfall, drought, storm surge etc. The aim of this research is to assess the impacts of climate change on fishersˊ livelihoods of Kishorganjhaor region, Bangladesh. The fisherˊ livelihood data were collected through semi-structured questionnaire interview and Focused Group Discussion (FGD) method. In Kishoreganjhaor region, natural disasters have increased due to climate change, that threat on fishersˊ l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In the study area, the average sex ratio of male and female were 56.67% and 43.33%, respectively. Islam et al (2020a) found 76.67% male and 23.23 % female in Kishoregonj Haor region. The age group of below 15 to 60 years which is considered as active and working group in the fishers" community and their religion ration were Islam 45% and Hindu 55% (Table 1).…”
Section: Demographic Information Of the Fishers In Louhajang Munshiganjmentioning
confidence: 84%
See 2 more Smart Citations
“…In the study area, the average sex ratio of male and female were 56.67% and 43.33%, respectively. Islam et al (2020a) found 76.67% male and 23.23 % female in Kishoregonj Haor region. The age group of below 15 to 60 years which is considered as active and working group in the fishers" community and their religion ration were Islam 45% and Hindu 55% (Table 1).…”
Section: Demographic Information Of the Fishers In Louhajang Munshiganjmentioning
confidence: 84%
“…According to Shill et al (2016), 80% fishers were Hindu in Munshiganj. But according to Islam et al (2020a) Muslims are dominant in Haor region in Kishoreganj. Most of the fishers have nuclear family (60%) and few have joint family (40%).…”
Section: Demographic Information Of the Fishers In Louhajang Munshiganjmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, fish reproduction (3% of records of changes in fisheries) and survival rates were gradually reduced. Climate change-related influences significantly impact fishes and their populations (Islam et al, 2020b;Rahaman et al, 2019Roessig et al, 2004.…”
Section: Fisheries Resources Variable Perception Of Fishermenmentioning
confidence: 99%